Prevalence of Dental Fear and Its Association with Oral Health Status Among School Children in Bosnia and Herzegovina: A Cross-Sectional Study - Jelena Eric; Bojana Davidovic; Rasa Mladenovic; Marko Milosavljevic; Ivana Dmitruk Miljevic; Ljiljana Bjelovic; Svjetlana Jankovic; Olivera Dolic; Brankica Davidovic (Medicina)
Background and Objective: This study aimed to examine the prevalence of dental fear among schoolchildren in Bosnia and Herzegovina, analyze the distribution of dental anxiety by gender, age, and place of residence in relation to perceived sources of fear, and evaluate its association with oral health status. Materials and Methods: The sample included 355 schoolchildren between the ages of 12 and 15. Data were gathered using a self-assessment questionnaire, a brief clinical oral examination, and the Children’s Fear Survey Schedule–Dental Subscale (CFSS-DS). Results: Clinical examinations showed that 87.61% of the children had dental caries, with a mean DMFT score of 3.75 (SD = 2.93). The prevalence of dental caries was significantly higher in the older group compared to the younger group (p < 0.01). Dental fear was present in 21.7% of the children, with a mean total CFSS-DS score of 27.50 (SD = 13.85). The most feared aspect among the children was “Choking” (73.8%), followed by “Injections” (63.7%) and “The noise of the dentist drilling” (52.1%). Children with dental fear had a significantly greater number of decayed and missing teeth, higher DMFT scores, and poorer gingival health and oral hygiene compared to those without dental fear (p < 0.01), even after adjusting for sociodemographic factors. Conclusions: The study found a moderate level of dental fear among Bosnian schoolchildren, with younger children and those from urban areas showing more fear of injections. It also showed a consistent link between dental anxiety and clinical factors such as caries, gum disease, and oral hygiene, even after adjusting for sociodemographic factors.